F. Engels and K. Marx on the Origin of Private Property and the State: One Concept or Two? - A. A. Koryakovtsev (Дискурс)
Introduction. The problem of incomplete coincidence of views of K. Marx and F. Engels has long been raised in marxology. On this topic, D. McLellan, M. Ryubel, K.N. Lubutin and P.N. Kondrashov spoke. However, they were limited to political economy and ontology. We will discuss the views of classics on the origin of private property and the state.Methodology and sources. In this article the textual analysis of the works «Origin of family, private property and state» by F. Engels and «Forms preceding capitalist production» and «Manuscripts of 1844» by K. Marx is taken. The author a dopts a historical-comparative approach, combining the ideas of the classics with those of later Marxist schools.Results and discussion. F. Engels explains the appearance of the state by class contradictions. However, it does not distinguish the concept of «class» from the concept of «estate» and ignores the fact that in the pre-capitalist era an individual opposed another individual as a representative of a community that provided a certain standard of living. In a paragraph entitled «Forms Preceding Capitalist Production» in the «Economic Manuscripts of 1857–1861», K. Marx describes how the state emerged as an organizer of forced community works. This coercion was determined not by socio-political factors but by natural factors. Labor created not only a social product, but also the very relationship of domination. We show the semantic connection of this concept with that which was embodied K. Marx in «Economical-philosophical manuscripts of 1844».Conclusion. In classical Marxism there is no unified concept of the origin of the state and private property; the concepts of K. Marx and F. Engels differ from each other in the interpretation of the role of labor in this process. F. Engels attributes a passive role to labor. For K. Marx, the role of labor is active: labor itself creates its opposite, private property, and with it the state, which arises and exists due to the limitations of labor.